1982
DOI: 10.1037/0003-066x.37.7.771
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Herrnstein's mathematical statement of the law of effect for behavior therapy.

Abstract: Herrnstein's mathematical statement of the law of effect improves on Skinner's view of reinforcement by asserting (a) that response rate varies hyperbolically with reinforcement rate and (b) that responding is governed not only by reinforcement obtained for responding but also by reinforcement obtained from all other concurrent sources. Data from infrahuman organisms and from humans in laboratory and clinical situations support this new view of reinforcement. Clinically, Herrnstein's equation requires a broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
111
1
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 16 publications
(28 reference statements)
1
111
1
1
Order By: Relevance
“…Put another way, to produce a given increment in response rate, a greater increment in reinforcement rate is required in a rich environment than in a lean one. McDowell (1981aMcDowell ( , 1982 (1974) actually designed an experiment to test matching theory in a natural human environment. The rest of the evidence is incidential; that is, the data were collected for other reasons.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Put another way, to produce a given increment in response rate, a greater increment in reinforcement rate is required in a rich environment than in a lean one. McDowell (1981aMcDowell ( , 1982 (1974) actually designed an experiment to test matching theory in a natural human environment. The rest of the evidence is incidential; that is, the data were collected for other reasons.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Most basic scientists would agree that matching theory has advanced significantly our understanding of how the environment governs behavior. In spite of its lengthy, active, and important history, however, and in spite of the publication of a number ofarticles that call attention to its clinical significance (Epling & Pierce, 1983;McDowell, 1981aMcDowell, , 1982Myerson & Hale, 1984), matching theory remains virtually unknown to applied behavior analysts. The purpose of this article is to describe matching theory, to explain its significance, and to show how it applies to human behavior in natural environments.…”
mentioning
confidence: 99%
“…The quantitative expression of this functional relation, in the form of the matching law, provided an important experimental account of choice behavior. Potential applications of the matching law have since been the focus of several theoretical papers (e.g., Epling & Pierce, 1983;McDowell, 1982;Myerson & Hale, 1984) and clinical studies showing that human choice varies positively with relative reinforcement (Conger & Killeen, 1974;Mace, Neef, Shade, & Mauro, 1994;Martens & Houk, 1989;McDowell, 1981).…”
mentioning
confidence: 99%
“…Pierce and Epling (1983), for example, reviewed the evidence for matching in the human operant literature, and others have suggested that matching has important implications for applied behavior analysis McDowell, 1981McDowell, , 1982Myerson & Hale, 1984a, 1984b Sidman, 1960, chaps. 8 and 9).…”
mentioning
confidence: 99%